Design and Implementation of Microstrip Patch Ultra-wide Band Antenna for Detection of UHF Partial Discharge. (August 2019) - Nawawi, Z; Sidik, M A B; Jambak, M I; Ahmad, N; Ahmad, M H; Kumar, C L G P; Waldi, E P; Aulia,
Abstract: Partial discharge (PD) is an electrical release or spark that occurs between two conducting electrodes that are not bridging, and it can occur at any points in the insulation system. PDs emit electromagnetic field radiation in the frequency range of 300 MHz to 1.5 GHz. Thus, it is more appropriate to detect and monitor partial discharge using an ultra-wideband antenna which offers more accuracy than the narrowband antenna. This paper proposes the design and implementation of a microstrip patch antenna which has been designed to possess wider detection performance of ultra-high frequency (UHF) PD signal. The PD spectra of the designed UWB antenna and the commercial whip antenna was compared and analyzed. The result shows that the UWB antenna can effectively detect the UHF PD signals that occur between two electrodes. As results, it is implied that PD measurement by using designed UWB antenna is found to suitable to detect the PD signals for online monitoring of high voltage equipment.